Optical navigation utilizing speed based algorithm selection - KOK BOON HOW; MAU MING YONG; LIM LAY CHENG JESSIE (2015)
Embodiments of method and systems are disclosed. An embodiment of a method for optical navigation involves generating light at a light source, directing the light to a navigation surface, detecting light reflected from the navigation surface toward a sensor array, and generating movement information, which is indicative of movement of the navigation surface relative to the sensor array, in response to the detected light. Generating the movement information involves determining the speed of the movement, comparing the speed of the movement to a movement threshold, selecting a processing algorithm from a plurality of processing algorithms in response to the comparison, and processing the movement information according to the selected processing algorithm. In an embodiment, the processing algorithms include an adaptive navigation algorithm and a sensor resolution adjustment algorithm.